JURNAL ILMU KESEHATAN JURNAL ILMU KESEHATAN STIKES DUTA GAMA KLATEN - Rr. Erni Kusuma Putri (STIKES DUTAGAMA KLATEN, 2022)
Cases of epilepsy in the world are about 50 million people, 80 % are found in developing countries. Epilepsy is characterized by repeated seizures for no reason. Treatment of epilepsy is with anti-epileptic drugs. The purpose of this study was to determine the percentage of use of anti-epileptic drugs in BPJS outpatient epilepsy patients at Purwogondo Hospital for the period January – December 2021. This research uses a descriptive method with a qualitative design. The data retrieval technique uses data from medical records. The sampling technique used is the total sampling on the medical record data of epilepsy patients in January – December 2021 as many as 353 prescription sheets. Data analysis using qualitative. Based on the results of research that epilepsy is widely suffered in male patients (60 %). The age range of people with epilepsy is dominated in children 6- 11 years (35 %) and the type of prescription visits in people with epilepsy is for one-week use of the drug (84 %). Based on the amount of drugs most prescribe at Purwogondo Hospital, namely phenytoin 10mg (31 %) with a single prescribing type (59 %).